Cadmium–Bacteria Complexation and Subsequent Bacteria‐Facilitated Cadmium Transport in Saturated Porous Media. Issue 5 (29th August 2019) - Li, Runwei; Zhang, Zhiming; Li, Simeng; Tang, Youneng; Wei, Changfu; Chen, Gang
Abstract : Cadmium (Cd) contamination is becoming a significant environmental concern due to its persistency in soil. In the subsurface, the fate and transport of Cd are significantly affected by the presence of organic carriers, including bacteria, which are ubiquitous. In this research, facilitated Cd transport by four different bacterial strains in zeolite was investigated by column experiments under three different Cd introduction scenarios (i.e., a Cd and bacteria mixture, Cd and bacteria introduced separately but simultaneously, and Cd added to the column, followed by bacterial flushing), through which Cd–bacteria complexes formed. In turn, Cd–bacteria complexation affected bacterial transport. Bacteria were least retarded when Cd was pre‐deposited, with mass recovery>90% for all strains. More Cd was recovered when introduced as a mixture with bacteria (i.e., Cd mass recovery ranging from 16 to 25%). Obtained bacteria and Cd breakthrough curves were simulated by the attachment–detachment model in Hydrus‐1D. Damkohler number and reversibility were both found to be suitable to control the mass recovery of Cd and bacteria in all investigated scenarios. Core Ideas: The introduction scenario significantly affected the transport of Cd and bacteria. Cd was most recovered when Cd–bacteria complexation was fully developed. Attachment, detachment, and convection competition determines Cd breakthrough.